Internship resources, mediating mechanisms, emotional exhaustion and career motivation in student teachers: a structural equation model - Abt, Yvonne; Holzäpfel, Lars; Oberfell, Heiko; Wirtz, Markus Antonius (Frontiers in Education, 2025)
During teaching internships, student teachers face a range of demands and new challenges that can affect their emotional wellbeing and motivation to pursue a teaching career. This study examined how various personal and contextual resources relate to emotional exhaustion and career motivation among student teachers during their internship semester using structural equation modeling. After validating the questionnaire structure with confirmatory factor analysis, a structural equation model was estimated (RMSEA = 0.052; CFI = 0.947) on data from 194 student teachers. Reflection, occupational insight, university mentoring support, and transparency showed indirect associations with emotional exhaustion and career motivation through self-efficacy and internship satisfaction as mediators. Furthermore, transparency also had a direct negative effect on career motivation. The model accounted for 40% of the variance in emotional exhaustion and 46% in career motivation. These findings underscore the importance of strengthening both personal and contextual resources to enhance teacher wellbeing and sustain career motivation in early teacher education.